Contribution of denervated muscle to contractures after neonatal brachial plexus injury: Not just muscle fibrosis. Issue 3 (11th December 2013) - Nikolaou, Sia; Liangjun, Hu; Tuttle, Lori J.; Weekley, Holly; Christopher, Wylie; Lieber, Richard L.; Cornwall, Roger
ABSTRACT Introduction: We investigated the contribution of muscle fibrosis to elbow flexion contractures in a murine model of neonatal brachial plexus injury (NBPI). Methods: Four weeks after NBPI, biceps and brachialis fibrosis were assessed histologically and compared with the timing of contracture development and the relative contribution of each muscle to contractures. Modulus of elasticity and hydroxyproline (collagen) content were measured and correlated with contracture severity. The effect of halofuginone antifibrotic therapy on fibrosis and contractures was investigated. Results: Elbow contractures preceded muscle fibrosis development. The brachialis was less fibrotic than the biceps, yet contributed more to contractures. Modulus and hydroxyproline content increased in both elbow flexors, but neither correlated with contracture severity. Halofuginone reduced biceps fibrosis but did not reduce contracture severity. Conclusions: Contractures after NBPI cannot be explained solely by muscle fibrosis, arguing for investigation of alternate pathophysiologic targets for contracture prevention and treatment. Muscle Nerve49:398–404, 2014